Energy cost of sport rock climbing in elite performers. Issue 1 (1st February 1999) - Booth, J; Marino, F; Hill, C; Gwinn, T
Abstract : OBJECTIVES: To assess oxygen uptake (VO2), blood lactate concentration ([La(b)]), and heart rate (HR) response during indoor and outdoor sport climbing. METHODS: Seven climbers aged 25 (SE 1) years, with a personal best ascent without preview or fall (on sight) ranging from 6b to 7a were assessed using an indoor vertical treadmill with artificial rock hand/foot holds and a discontinuous protocol with climbing velocity incremented until voluntary fatigue. On a separate occasion the subjects performed a 23.4 m outdoor rock climb graded 5c and taking 7 min 36 s (SE 33 s) to complete. Cardiorespiratory parameters were measured using a telemetry system and [La(b)] collected at rest and after climbing. RESULTS: Indoor climbing elicited a peak oxygen uptake (VO2climb-peak) and peak HR (HRpeak) of 43.8 (SE 2.2) ml/kg/min and 190 (SE 4) bpm, respectively and increased blood lactate concentration [La(b)] from 1.4 (0.1) to 10.2 (0.6) mmol/l (p < 0.05). During outdoor climbing VO2 and HR increased to about 75% and 83% of VO2climb-peak and HRpeak, respectively. [La(b)] increased from 1.3 (0.1) at rest to 4.5 mmol/l (p < 0.05) at 2 min 32 s (8 s) after completion of the climb. CONCLUSIONS: The results suggest that for elite climbers outdoor sport rock climbs of five to 10 minutes' duration and moderate difficulty require a significant portion of the VO2climb-peak. The higher HR and VO2 for outdoor climbing and the increased [La(b)] could be the result of repeated isometric contractions, particularly from the arm and forearm muscles.